Dielectric properties of Nb-doped CaCu3Ti4O12 electroceramics measured at high frequencies - Sulaiman, Muhammad Azwadi; Hutagalung, Sabar D.; Ain, Mohd Fadzil; Ahmad, Zainal A. (2010)
In this work, Nb dopant was introduced into CaCu3Ti4O12 (CCTO) electroceramic in order to improve the dielectric properties. The CCTO electroceramic was prepared using the solid state reaction method. An X-ray diffractometer (XRD) analysis proved the formation of a single CCTO phase after sintering at 1040◦C for 10h. Abnormal grain growth was observed in undoped CCTO and 1mol% Nb-doped CCTO. Normal grain growth was produced at Nb dopant levels higher than 3mol%. Dielectric properties were measured at a frequency range of 1MHzto 1GHz. It was found that CCTO doped with 1mol% Nb gave the highest dielectric constant of 18,000 at 1MHz. Meanwhile, the lowest dielectric loss (0.31) at 1MHz was given by CCTO doped with 10mol% Nb. The dielectric constant between 10MHz and 1GHz was almost stable with values at around 500.